POTENSI POLA ALIRAN MUDIK PADA MASA PANDEMI COVID-19 - Ari Purwanto Sarwo Prasojo; Yulinda Nurul Aini; Dwiyanti Kusumaningrum (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Millions of people in Indonesia traditionally return to their home town every year in a tradition called